Serotypes of Streptococcus pneumoniae in Children Aged <5 Years Hospitalized With or Without Pneumonia in Developing and Emerging Countries: A Descriptive, Multicenter Study. (25th June 2019) - Dananché, Cédric; Paranhos-Baccalà, Gláucia; Messaoudi, Mélina; Sylla, Mariam; Awasthi, Shally; Bavdekar, Ashish; Sanghavi, Sonali; Diallo, Souleymane; Pape, Jean-William; Rouzier, Vanessa; Chou, Monidarin; Eap, Tekchheng; et al.
Abstract: Background: Improving knowledge regarding Streptococcus pneumoniae distribution in pneumonia cases is important to better target preventive and curative measures. The objective was to describe S. pneumoniae serotypes in children with or without pneumonia Methods: It was a case-control study carried out in 8 developing and emerging countries between 2010 and 2014. Cases were children aged <5 years admitted to the hospital for pneumonia. Controls were children admitted for surgery or routine outpatient care. Results: In nasopharyngeal samples, S. pneumoniae were detected in 68.2% of the cases and 47.5% of the controls ( P < .001). Nasopharyngeal carriage was associated with a higher risk of being a case in 6/8 study sites (adjusted odds ratio ranged from 0.71 [95% confidence interval [CI], .39–1.29; P = .26] in India [Pune/Vadu] to 11.86 [95% CI, 5.77–24.41; P < .001] in Mongolia). The 13-valent pneumococcal conjugate vaccine (PCV13) serotypes were more frequently detected in cases with nasopharyngeal carriage (67.1%) than in controls with nasopharyngeal carriage (54.6%), P < .001. Streptococcus pneumoniae was detected in blood by polymerase chain reaction in 8.3% of the cases. Of 34 cases with an S. pneumoniae serotype detected in blood, 27 (79%) had the same serotype in the nasopharyngeal sample. Conclusions: The results confirm the assumption that the isolate carrying or causing disease in an individual is of the same serotype. Most serotypes independently associated with nasopharyngeal carriage or pneumonia are covered by PCV13, suggesting that increased PCV coverage would reduce the burden of S. pneumoniae –related pneumonia. Abstract : Nasopharyngeal carriage of Streptococcus pneumoniae was less frequently detected in controls compared to cases. The dominant serotypes were included in 13-valent pneumococcal conjugate vaccine. The pneumococci serotype detected in blood of approximately 80% of cases was detected in nasal carriage.